8.5x-6.1=-7.1
40x-6.1=-7.1
40x=-7.1+6.1
40x=-1
solution= x= -0.025
Answer:
81/10
Step-by-step explanation:
i just figured it out i really don't have one but i hope it helps
Answer:
2; -2
Step-by-step explanation:
|7-9| = |-2| = 2
|7|-9= 7 - 9 = -2
Hey there!!
Given equation :
... 3x - 2 + 5x = 4x + 5 - 2x
Combining like terms :
... 8x - 2 = 2x - 5
Subtracting 2x on both sides :
... 6x - 2 = - 5
Adding 2 on both sides :
... 6x = - 3
Dividing by 6 on both sides :
... x = -1/2 = -0.5
Hence, the answer is -0.5
Hope my answer helps!
ince the problem is only asking for 4 years, we can just calculated it out year by year. Recall the formula for compounding interest: A = P(1+r)n, where A is the total amount, P is the principle (amount you start with), r is the interest rate per period of time, and n is the number of periods (in this case, r is annual interest rate, so n is number of years). At the beginning (Year 0), Lou starts off with 10000: A = 10000 At the end of Year 1, Lou earned interest on that amount, plus he has deposited another 5000: A = 10000(1.08) + 5000 End of Year 2, Lou's interest from the year 0 amount has compounded, he has started earning interest on the amount deposited last year, and he deposits another 5000: A = 10000(1.08)2 + 5000(1.08) + 5000 End of Year 3, same idea. Lou has earned compounding interest on all existing deposits, and deposits another 5000: A = 10000(1.08)3 + 5000(1.08)2 + 5000(1.08) + 5000 End of Year 4, same idea: A = 10000(1.08)4 + 5000(1.08)3 + 5000(1.08)2 + 5000(1.08) + 5000 = 36135.45